Pengaruh Budaya Perusahaan terhadap Kinerja Karyawan pada PT Fuji Technica Indonesia - Lestari, Ayu; Kurniawati, Kurniawati; Rahayu, Tutik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was motivated by wanting to know the extent to which factors influence employee performance at PT Fuji Technica Indonesia. One of the variables that researchers use to examine the influence of employee performance is company culture. The purpose of this research is to explain or explain the influence of company culture variables on employee performance. This research was carried out at PT Fuji Technica Indonesia from June to September 2023. The research method used was quantitative with associative techniques. The population at PT Fuji Technica Indonesia was 400 people. The samples taken were 80 people using the Slovin sampling technique. Based on the calculation results shown in table 4.5, a correlation coefficient of r = 0.767 and a determination coefficient of R = r2 = 0.588 were obtained. Testing the significance of the correlation obtained tcount (10.551 > t table (2.000) at  = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between Corporate Culture and Employee Performance can be accepted. This means that the better the Corporate Culture will be followed by high Employee Performance. Meanwhile, the coefficient of determination of 0.588 shows that 58.8% of the variation in Employee Performance can be explained by variations in Corporate Culture, the remaining 41.2% is determined by other factors outside Corporate Culture. Based on the results of calculations to develop an equation model In the regression between Company Culture (X) and Employee Performance (Y), the constant α = 3.041 and the regression coefficient β = 1.132 were obtained. Thus, the influence between the independent variable X and the dependent variable Y can be expressed in a simple linear regression equation model as follows: Ý = 3.041 + 1.132 This shows that the regression equation model is significant. The linearity test results obtained Fcount (1.25) < Ftable (1.90) at  = 0.05. These results indicate that the regression equation is linear. Based on the test results above, the regression equation Ý = 3.041+ 1.132X can be used to explain the form of a linear relationship between Company Culture and Employee Performance. This relationship shows that there is a direction of change in the trend of respondent employee performance due to company culture.